PENGARUH PEMBERIAN MOTIVASI DAN DISIPLIN KERJA TERHADAP SEMANGAT KERJA KARYAWAN DI MASA PANDEMI PADA BANK RIAU KEPRI CABANG PEKANBARU - Yuni Azizah; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to influence the provision of work motivation and work discipline on the morale of employees of Bank Riau Kepri Pekanbaru Branch. The variable giving work motivation as a variable (X1), work discipline as a variable (X2) and work enthusiasm as a variable (Y). This research method is descriptive quantitative using SPSS 22 program, where the sample used is 81 employees using saturated sampling technique and data collection techniques using questionnaires. From the results of data analysis which includes validity test, reliability test, determination test, simple linear regression test and multiple linear regression test, t test, f test so that it can be concluded that the provision of work motivation partially has a positive and significant effect on employee morale, work discipline partially positive and significant effect on employee morale, the provision of work motivation and employee work discipline simultaneously significant effect on morale in employees of Bank Riau Kepri Pekanbaru Branch.. Keywords: Providing work motivation and work discipline, work spirit.